(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
Affective computing is a discipline of artificial intelligence that attempts to develop computational methods to recognize human emotions and generate synthetic emotions. Incorporating emotions into intelligent agents can be advantageous in different areas; emotions can make agents more credible so they can play a better role in various interactive systems to simulation level. Emotions would also play a functional role in complex systems, regulating interactions among agents. Different authors are trying to improve the interaction among intelligent agents in multiagent systems; an example is the MASOES affective model, which through the generation of emotions promotes different behaviors patterns. Although this affective model has already been formally verified at the design level, its verification is still a pending action. In this paper, we are presenting the MASOES affective model on a multiagent system, which has been verified in both, individual and collaborative mode.